Perwujudan Desa Cerdas dalam Pembangunan Berkelanjutan: Penguatan Literasi, Kapabilitas, dan Kesehatan Masyarakat Rejoyoso - Raya, Dian Anisa; Fadil, Cholid; Imaningsih, Niniek (VISA: Journal of Vision and Ideas, 2024)
This research aims to evaluate the education, health, and economic conditions of the community in Rejoyoso Village, Malang Regency, East Java, and to design and implement empowerment programs to improve the quality of human resources and village development. Focusing on literacy, health, and economics, this research seeks to overcome the challenges of access and awareness of the importance of holistic human development. The research approach involves collaboration with Galeri Kreatif as a local partner, using the Certified Independent Study Internship Program (MSIB) and Aqil Learning Space (RBA) as a platform for empowerment programs. Data was collected through literacy meetings, field observations, and interviews with village officials and collaborators. The results show that Rejoyoso Village has economic potential in the agricultural sector and its human resources. However, limited access to education and health, especially among children and the elderly, affects the quality of human resources. Early marriage and lack of access to health care are serious issues. The empowerment program designed includes literacy strengthening, primary health care, and branding improvement for Opak Santri MSMEs. The program involves activities such as workshops, mentoring, and counseling. Evaluation through impression-feedback forms and reflection sheets shows a positive response from participants, and a positive impact is seen in increased participation in education and health activities. The conclusion of the research shows that through collaboration between various parties, including local government, educational institutions, and the community, empowerment programs can successfully improve literacy, health, and the economy in Rejoyoso Village. Continuous evaluation and collaboration are key to the sustainability of empowerment programs and the overall improvement of human resources and village development.